Parents in the spotlight parenting practices and support from a comparative perspective - Betz, Tanja 1976-; Honig, Michael-Sebastian 1950-; Ostner, Ilona 1947- (Zeitschrift für Familienforschung. Sonderheft, 2017)
Children and parents have become a focus of debates on ‘new social risks’ in European welfare states. Policymaking elites have converged in defining such risks, and they have outlined new forms of parenting support to better safeguard children and activate their potential. Increasingly, parents are suspected of falling short of public expectations. Contributors to this special issue scrutinize this shift towards parenting as performance and analyse recent forms of parenting support. Quelle=Source: Klappentext/Verlag=Publisher.